Analysis of a poxtA- and optrA-co-carrying conjugative multiresistance plasmid from Enterococcus faecalis. (19th March 2019) - Hao, Wenbo; Shan, Xinxin; Li, Dexi; Schwarz, Stefan; Zhang, Su-Mei; Li, Xin-Sheng; Du, Xiang-Dang
Abstract: Objectives: To investigate the presence and transferability of the poxtA gene and identify the genetic context of poxtA in two enterococcal plasmids from swine. Methods: MICs were determined by broth microdilution. A total of 114 porcine enterococci with florfenicol MICs of ≥16 mg/L were screened for the presence of the poxtA gene by PCR. Transferability of poxtA was investigated by conjugation and transformation. The poxtA -carrying plasmids were completely sequenced using the Illumina Miseq and PacBio RSII platform. The presence of circular intermediates was examined by inverse PCR. Results: The poxtA gene was present in 57.9% (66/114) of the florfenicol-resistant porcine enterococci. Two poxtA -carrying plasmids, pE035 and pE076, were identified. The conjugative 121524 bp plasmid pE035 carried poxtA and optrA along with the resistance genes erm (A), erm (B), aac (A)- aph (D), lnu (G), fexB, dfrG and bcr ABDR. Three mobile elements, comprising a mobile dfrG locus, a mobile bcr ABDR locus and an unconventional circularizable structure containing aac (A)- aph (D), were located on this plasmid and all proved to be active by inverse PCR. The non-conjugative 19832 bp plasmid pE076 only carried poxtA and fexB . After transfer, both the transconjugant and the transformant displayed elevated MICs of the respective antimicrobial agents. Conclusions: To the best of our knowledge, this is the first report of the co-location of the oxazolidinone resistance genes poxtA and optrA on a conjugative multiresistance plasmid from a porcine enterococcal strain. In addition, the presence of three mobile elements in such a plasmid will aid in the persistence and dissemination of poxtA and optrA among enterococci.